2013
DOI: 10.1186/1471-2415-13-75
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of choroidal thickness in a case of carotid cavernous fistula: a case report and a review of the literature

Abstract: BackgroundTo measure the alterations of the choroidal thickness in Carotid cavernous fistula (CCF) using enhanced depth imaging optical coherence tomography (EDI-OCT).Case presentationA 64-year-old woman was referred to us for redness, exophthalmos and visual disturbance in her right eye. She was diagnosed with CCF by magnetic resonance imaging (MRI) and magnetic resonance angiography.Observations; Embolization resulted in improvement of ocular symptoms, and there was a reduction of the subfoveal choroidal thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
(14 reference statements)
2
18
0
Order By: Relevance
“…It has been published that choroidal thickness increases in cases of AVF, decreasing after its closure. 7 In our report, choroidal thickness could only be measured in the second case, and we measured a decrease in 134 μm during our follow-up, as previously published.…”
Section: Discussionsupporting
confidence: 70%
“…It has been published that choroidal thickness increases in cases of AVF, decreasing after its closure. 7 In our report, choroidal thickness could only be measured in the second case, and we measured a decrease in 134 μm during our follow-up, as previously published.…”
Section: Discussionsupporting
confidence: 70%
“…EDI-OCT is a noninvasive technique that is used to evaluate choroidal thickness and morphology in these diseases [ 2 ]. Shinohara et al [ 3 ], have already reported that the relationship between an increased choroidal thickness by EDI-OCT and choroidal congestion in CCF by using fluorescein angiography, laser speckle flowgraphy and brain angiography before and after embolization of the CCF, however, serous retinal detachment was not present.…”
Section: Discussionmentioning
confidence: 99%
“…39 Shinohara et al reported that the choroidal thickness of a patient with carotid cavernous stula (CCF) was increased secondary to the superior orbital vein (SOV) congestion. 40 They suggested that it may cause may lead to increased choroidal pressure and may increase the subfoveal CT. In the present study, we observed that there were signi cant differences in subfoveal CT variations between the two groups.…”
Section: Discussionmentioning
confidence: 99%